Professional Acquisition of M. bovis in Calabria Region (Southern Italy): A Challenging Case of Osteomyelitis in a Migrant Patient from Bulgaria. (14th July 2015) - Quirino, Angela; Torti, Carlo; Strazzulla, Alessio; Nisticò, Salvatore; Galati, Luisa; Barreca, Giorgio Settimo; Lamberti, Angelo Giuseppe; Berardelli, Giuseppina; Pacciarini, Maria; Gasparini, Giorgio; Pisani, Vincenzo; Gambardella, Antonio; et al.
Abstract : We report herein the first case of a coinfection with Brucella spp., M. bovis, and Enterobacter cloacae in a butcher who moved from Bulgaria to Italy. Molecular typing suggested professional acquisition of M. bovis in Italy. So, surveillance and preventive measures need to be implemented.